Modified CuZnAl catalyst, preparation method thereof and application of modified CuZnAl catalyst in maleic anhydride hydrogenation
By introducing transition metals such as Fe, Co, Ni, etc. into the CuZnAl catalyst and coating them with nanocarbon materials, the problems of insufficient hydrogenation capacity and excessive hydrogenolysis reaction are solved, and the efficiency and stability of the maleic anhydride hydrogenation reaction are improved. Reduced production costs.
Patent Information
- Application Number
- CN202411311311.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-03
AI Technical Summary
The existing CuZnAl catalysts have problems such as insufficient hydrogenation capacity, serious excessive hydrogenation reaction, high cost and poor stability in the process of hydrogenation of malic anhydride to make γ-butyrolactone, especially in the rapid deactivation of the catalyst under high load conditions.
Introduce group VIII transition metals such as Fe, Co, Ni, etc., and coat these metals through nanocarbon materials to enhance the H2 adsorption and dissociation ability of the catalyst, and prevent the accumulation of reaction heat through the thermal conductivity of nanocarbon materials to form nanocarbon materials and transition metals. Modified CuZnAl catalyst.
It significantly improves the hydrogenation capacity and heat transfer performance of the catalyst, extends the life of the catalyst, improves the selectivity and production capacity of γ-butyrolactone, reduces production costs, and achieves long-term and stable operation.
Smart Images

Figure CN119236947A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fine chemicals, and in particular relates to a modified CuZnAl catalyst, a preparation method thereof and an application method thereof in the reaction of preparing gamma-butyrolactone by hydrogenating maleic anhydride. Background Art
[0002] γ-Butyrolactone is an important organic chemical raw material and intermediate, widely used in medicine, pesticides, fine chemicals and other fields. It can be used to synthesize high value-added chemicals such as pyrrolidone, N-methylpyrrolidone, ethylpyrrolidone, 1,4-butanediol, tetrahydrofuran, etc. At the same time, γ-butyrolactone has the advantages of high boiling point, strong solubility, high electrolysis rate and good stability. It is an excellent solvent and is often used as an extractant, absorbent and electrolyte solution.
[0003] At present, there are two main methods for industrial production of γ-butyrolactone: 1,4-butanediol dehydrogenation and maleic anhydride hydrogenation. 1,4-butanediol dehydrogenation is the main route for industrial production of γ-butyrolactone. 1,4-Butanediol is produced from calcium carbide-formaldehyde, maleic anhydride, propylene, and butadiene through a multi-step complex reaction process, resulting in high production costs for γ-butyrolactone. Maleic anhydride hydrogenation bypasses the complex 1,4-butanediol process and has the advantages of short process route, low energy consumption, adjustable products, and economic and environmental protection.
[0004] du Pont (1953) first reported the method of preparing γ-butyrolactone, 1,4-butanediol and tetrahydrofuran by hydrogenation of maleic anhydride, using catalysts such as Raney nickel, Raney cobalt, Ni-Mo, Co-Mo, Ni-Cr-Mo (US2772291A, US2772292A, US2772293A).
[0005] Mitsubishi Corporation reported a method for preparing γ-butyrolactone, tetrahydrofuran and 1,4-butanediol by catalytic hydrogenation of C4 dicarbonyl acids and their anhydrides (including maleic acid, fumaric acid, succinic acid, maleic anhydride and succinic anhydride), using Ni-Re, Ni-Mo, Ni-W and Ni-Co-Th catalysts (US3492314A, GB1200979A, DE1901870A1, DE1939882A1, US3758512A, DE2129834A1 and JP49032439B).
[0006] Kao Soap Company reported a method for producing γ-butyrolactone or tetrahydrofuran by gas phase hydrogenation of maleic anhydride, using a Cu-Cr catalyst or a Cu-Zn-Cr and silicon aluminum oxide composite catalyst (US3580930A, DE2332906A1).
[0007] GAF reported a method for producing γ-butyrolactone by gas-phase hydrogenation of maleic anhydride using Cu-Pd or Cu-Pt catalysts. Under normal pressure and 240-310°C, the maleic anhydride conversion rate was greater than 92% and the γ-butyrolactone selectivity was greater than 92% (GB1534136, US4083809A).
[0008] The Shanxi Coal Chemistry Research Institute of the Chinese Academy of Sciences has developed a process for preparing γ-butyrolactone by hydrogenation of maleic anhydride at atmospheric pressure in the gas phase. The process uses a Cu-Zn-Al catalyst modified with Ba and Pd. After the maleic anhydride vapor and hydrogen are mixed, they pass through a fixed bed reactor. The reaction temperature is 250-320°C, the reaction pressure is less than 0.05MPa, the molar ratio of hydrogen to maleic anhydride is 10-200, and the weight space velocity of maleic anhydride liquid is 0.02-0.26h -1 The single-pass conversion rate of maleic anhydride is 100%, and the selectivity of γ-butyrolactone can reach 93-98%, but the space-time yield of the catalyst is less than 0.1h -1 , and needs to be regenerated; in addition, this catalyst needs to be modified by precious metal Pd to achieve long-term stability, which is costly and not economical; and the applicable conditions of this catalyst are low-load feed conditions with a maleic anhydride weight space velocity of 0.02 to 0.26 g / g-cat. / h. Under high-load feed conditions without precious metal Pa or with a maleic anhydride weight space velocity of more than 0.5 g / g-cat. / h, the traditional CuZnAl catalyst will be quickly deactivated, and the stable operation is only about 140h (CN1298759A, CN1095400C).
[0009] The hydrogenation of maleic anhydride to produce γ-butyrolactone is a high-temperature (250-300℃), highly exothermic (-211kJ / mol), multi-stage series reaction. γ-Butyrolactone is an intermediate product, and its selectivity is difficult to control. If the catalyst hydrogenation capacity is insufficient and the raw material conversion is insufficient, acidic compounds such as maleic acid, succinic acid, butyric acid, and propionic acid will be produced, corroding the catalyst and causing the active metal to dissolve and deactivate; if excessive hydrogenation or polymerization occurs, products such as methanol, propanol, butanol, 1,4-butanediol, tetrahydrofuran, and oligomers will be produced, as shown in the figure below.
[0010]
[0011] At the same time, maleic anhydride is heat-sensitive and easily cokes at high temperatures. These raw material characteristics and reaction characteristics lead to poor selectivity and extremely poor stability of the catalyst. To obtain excellent maleic anhydride hydrogenation to γ-butyrolactone reaction performance, it is necessary to accurately control the adsorption and hydrogenation performance of the catalyst on maleic anhydride raw materials. Among the many maleic anhydride hydrogenation catalysts, Ni and Co catalysts have strong hydrogenation ability, but the CC hydrogenolysis reaction is also too high, and the selectivity of byproducts methane and methanol is too high, while the CuZnAl catalyst has moderate hydrogenation ability and weak hydrogenolysis ability, which is suitable for direct hydrogenation of maleic anhydride to γ-butyrolactone. However, there are no large-scale application cases of CuZnAl-catalyzed direct hydrogenation of maleic anhydride in industry. Mainly due to the above characteristics of maleic anhydride and maleic anhydride hydrogenation reactions, the CuZnAl catalyst is severely deactivated during the reaction, repeatedly regenerated, and the production cost is too high. To solve the above problems, it is necessary to improve the maleic anhydride hydrogenation activity of the CuZnAl catalyst and inhibit the occurrence of excessive hydrogenolysis reactions.
[0012] In view of the above problems, the present invention introduces Group VIII transition metals such as Fe, Co, and Ni into the CuZnAl catalyst to increase the H2 adsorption and dissociation ability of the catalyst, overflow the active H atoms to the Cu surface, and increase the hydrogenation ability of the catalyst; and the Fe, Co, and Ni metals are coated with nano-carbon materials to prevent them from adsorbing and dissociating maleic anhydride molecules and inhibiting the occurrence of hydrogenolysis reactions. At the same time, the nano-carbon material has excellent thermal conductivity, and in the process of efficient conversion of maleic anhydride, the reaction heat can be quickly removed to prevent the sintering of the active metal of the catalyst. Therefore, the present invention provides a CuZnAl catalyst modified by nano-carbon materials and transition metals and a preparation method thereof, and provides an application method of the catalyst for hydrogenating maleic anhydride to produce γ-butyrolactone. Summary of the invention
[0013] The purpose of the present invention is to overcome the problems of excessive maleic anhydride adsorption, insufficient hydrogenation capacity, high cost, and poor stability under high-load feed conditions in the existing maleic anhydride hydrogenation catalyst to produce γ-butyrolactone, and to provide a high-efficiency maleic anhydride hydrogenation catalyst to produce γ-butyrolactone. The present invention is greatly improved in hydrogenation, heat transfer, and high-capacity or high-load long-term stability, greatly improving the efficiency of the catalyst. The present invention also provides a method for preparing the catalyst, and the use of the catalyst in the reaction of maleic anhydride hydrogenation to produce γ-butyrolactone. With the help of the improved catalyst hydrogenation and heat transfer characteristics, the activity and selectivity of maleic anhydride hydrogenation to produce γ-butyrolactone are greatly improved.
[0014] In the first aspect, the present invention provides a CuZnAl catalyst modified by nanocarbon material and transition metal, wherein the catalyst contains CuO, ZnO, Al2O3, transition metal and nanocarbon material, wherein the transition metal is at least one of Fe, Co and Ni; the nanocarbon material is at least one of fullerene, carbon nanocage, single-walled nanotube and multi-walled carbon nanotube; and the transition metal is coated in the nanocarbon material structure.
[0015] In a second aspect, the present invention provides a method for preparing the CuZnAl catalyst modified by nano-carbon material and transition metal, the method comprising the following steps:
[0016] (1) using a carbon-containing gas to carbonize a transition metal raw material by chemical vapor deposition to prepare a nano-carbon-coated transition metal composite material;
[0017] (2) co-precipitating a solution containing three elements of Cu, Zn and Al to prepare an unmodified CuZnAl precipitation precursor;
[0018] Alternatively, a solution containing the two elements of Cu and Zn is subjected to a coprecipitation treatment, and pseudo-boehmite is added before or after the coprecipitation treatment to prepare an unmodified CuZnAl precipitation precursor;
[0019] Alternatively, a solution containing three elements of Cu, Zn and Al is co-precipitated with the nano-carbon-coated transition metal composite material obtained in step (1) to prepare a nano-carbon-coated transition metal-modified CuZnAl precipitation precursor;
[0020] (3) drying, calcining and shaping the unmodified CuZnAl precipitate precursor obtained in step (2) to obtain an unmodified CuZnAl catalyst;
[0021] Alternatively, the nanocarbon-coated transition metal composite material obtained in step (1) is added to the unmodified CuZnAl precipitate precursor obtained in step (2), followed by drying, calcining, and molding to obtain the CuZnAl catalyst modified with the nanocarbon material and the transition metal;
[0022] Alternatively, the nano-carbon-coated transition metal-modified CuZnAl precipitate precursor obtained in step (2) is dried, calcined, and formed to obtain the CuZnAl catalyst modified by the nano-carbon material and the transition metal;
[0023] (4) if no nano-carbon-coated transition metal composite material is added in steps (2) and (3), the unmodified CuZnAl catalyst obtained in step (3) is mixed evenly with the nano-carbon-coated transition metal composite material obtained in step (1), and the mixture is molded to obtain the CuZnAl catalyst modified with the nano-carbon material and the transition metal;
[0024] Alternatively, a soluble salt solution of transition metals Fe, Co, and Ni is added to the unmodified CuZnAl catalyst obtained in step (3), dried and calcined, carbonized in a carbon-containing atmosphere, and finally molded to obtain the CuZnAl catalyst modified with nano-carbon material and transition metal.
[0025] In a third aspect, the present invention provides use of the CuZnAl catalyst modified by nano-carbon material and transition metal for preparing γ-butyrolactone by catalyzing maleic anhydride hydrogenation reaction.
[0026] In a fourth aspect, the present invention provides a method for preparing γ-butyrolactone by catalyzing the hydrogenation of maleic anhydride using the above-mentioned CuZnAl catalyst modified by nanocarbon material and transition metal, the method comprising placing the CuZnAl catalyst particles modified by nanocarbon material and transition metal in a reactor, passing maleic anhydride raw material and hydrogen into the reactor to contact with the catalyst, and converting maleic anhydride into γ-butyrolactone by hydrogenation of the catalyst.
[0027] Beneficial Effects
[0028] The CuZnAl catalyst modified by nano-carbon material and transition metal provided by the present invention has many beneficial properties: high economy, high thermal conductivity, excellent mass transfer performance, enhanced hydrogenation performance and resistance to physical and chemical wear, especially high thermal conductivity and high wear resistance can maintain the high activity, high selectivity, high productivity and long-term stability of the catalyst in a strong exothermic reaction.
[0029] The catalyst involved in the present invention and its application in maleic anhydride hydrogenation reaction have excellent hydrogenation and heat transfer capabilities, can efficiently convert maleic anhydride into gamma-butyrolactone, and show high space-time yield, high gamma-butyrolactone selectivity and long-term stability in the continuous hydrogenation process under high-load feed conditions with a maleic anhydride weight space velocity of more than 0.5 g / g-cat. / h.
[0030] Under the reaction conditions of 200-300° C., 0.1-2.0 MPa and maleic anhydride weight space velocity of 1-3 g / g-Cat. / h, by using the catalyst of the present invention, the conversion rate of maleic anhydride is about 100%, the selectivity of γ-butyrolactone is as high as 84%-98.5% (preferably above 94%, more preferably above 95%, further preferably above 97%, and even up to 98.5%), the catalyst life is 500h-4300h (preferably above 1000h, more preferably above 2000h, further preferably above 3000h, and even up to 4000h), and the γ-butyrolactone production capacity of the catalyst is 1000-3500g / g-cat (preferably above 1000g / g-cat, more preferably above 2000g / g-cat, further preferably above 3000g / g-cat, and even up to 3500g / g-cat). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the SEM picture of the sample prepared in Example 1.
[0032] Figure 2This is a TEM image of the sample prepared in Example 1.
[0033] Figure 3 This is the XRD pattern of the sample prepared in Example 1.
[0034] Figure 4 This is the SEM picture of the sample prepared in Example 2.
[0035] Figure 5 This is the TEM image of the sample prepared in Example 2.
[0036] Figure 6 This is the XRD pattern of the sample prepared in Example 2.
[0037] Figure 7 This is the SEM photograph of the sample prepared in Example 3.
[0038] Figure 8 TEM photo of the sample prepared in Example 3
[0039] Fig. 9 This is the XRD pattern of the sample prepared in Example 3.
[0040] Fig.10 SEM photo of the sample prepared in Example 4
[0041] Fig.11 This is the XRD pattern of the sample prepared in Example 4.
[0042] Fig.12 SEM photo of the sample prepared in Example 5
[0043] Fig.13 This is the XRD pattern of the sample prepared in Example 5.
[0044] Fig.14 SEM photo of the sample prepared in Example 7
[0045] Fig.15 This is the XRD pattern of the sample prepared in Example 7.
[0046] Fig.16 This is the SEM photograph of the sample prepared in Example 13.
[0047] Fig.17 This is the XRD pattern of the sample prepared in Example 13. DETAILED DESCRIPTION
[0048] In this document, unless otherwise specified, the term "specific surface area" means the specific surface area measured by the BET method (Brunauer-Emmet-Teller), and the measurement method is described in standard NFX 11-621; the term "particle distribution" means the particle size distribution, which is measured by light scattering.
[0049] As used herein, unless otherwise specified, the terms "catalyst active phase", "active component", "active phase metal", "active metal" and "metal active phase" are used interchangeably to refer to the metal component of the active phase of the catalyst.
[0050] In some embodiments, the present invention provides a CuZnAl catalyst modified by nanocarbon material and transition metal, wherein the catalyst contains CuO, ZnO, Al2O3, transition metal and nanocarbon material, wherein the transition metal is at least one of Fe, Co and Ni; the nanocarbon material is at least one of fullerene, carbon nanocage, single-walled nanotube and multi-walled carbon nanotube; the transition metal is coated in the nanocarbon material structure.
[0051] In a preferred embodiment, the catalyst consists of CuO, ZnO, Al2O3, transition metals and nano-carbon materials.
[0052] In a preferred embodiment of the catalyst active component, relative to the total mass of the CuZnAl catalyst modified by nano-carbon material and transition metal, the mass content of CuO is 15-70wt%, preferably 25-60wt%, and more preferably 40-50wt%; the mass content of ZnO is 5-60wt%, preferably 15-50wt%, and more preferably 30-40wt%; the mass content of Al2O3 is 2-30wt%, preferably 5-20wt%, and more preferably 8-15wt%; the mass content of the transition metal is 0.001-5wt%, preferably 0.01-2wt%, and more preferably 0.1-1wt%; the mass content of the carbon material is 0.5-20wt%, preferably 0.1-10wt%, and more preferably 1-5wt%.
[0053] In a preferred embodiment, the elemental mass composition of the CuZnAl catalyst modified by nano-carbon material and transition metal is selected from the following:
[0054] CuO / ZnO / Al2O3 / Fe / C=45.9 / 46.0 / 6.9 / 0.02 / 1.2;
[0055] CuO / ZnO / Al2O3 / Co / C=45.7 / 45.8 / 6.9 / 0.006 / 1.6;
[0056] CuO / ZnO / Al2O3 / Ni / C=55.4 / 35.7 / 5.6 / 0.02 / 3.3;
[0057] CuO / ZnO / Al2O3 / Fe / C=46.2 / 42.4 / 8.9 / 0.08 / 2.4;
[0058] CuO / ZnO / Al2O3 / Co / C=68.3 / 23.1 / 7.3 / 0.005 / 1.3;
[0059] CuO / ZnO / Al2O3 / Ni / C=46.0 / 43.8 / 9.6 / 0.003 / 0.6;
[0060] CuO / ZnO / Al2O3 / Fe / C=44.4 / 42.1 / 9.2 / 0.5 / 3.8;
[0061] CuO / ZnO / Al2O3 / Co / C=45.1 / 42.8 / 9.3 / 0.2 / 2.6;
[0062] CuO / ZnO / Al2O3 / Ni / C=35.4 / 33.6 / 7.4 / 3.8 / 19.8.
[0063] In the present invention, in the CuZnAl catalyst modified by nanocarbon material and transition metal, the transition metal is coated in the nanocarbon material structure, which can also be called a nanocarbon-coated transition metal composite material, that is, the nanocarbon-coated transition metal composite material is at least one of Fe@fullerene, Co@fullerene, Ni@fullerene, Fe@carbon nanocage, Co@carbon nanocage, Ni@carbon nanocage, Fe@single-walled carbon nanotube, Co@single-walled carbon nanotube, Ni@single-walled carbon nanotube, Fe@multi-walled carbon nanotube, Co@multi-walled carbon nanotube, Ni@multi-walled carbon nanotube and the like.
[0064] In the present invention, transition metal@nanocarbon material (eg, Fe@fullerene) refers to transition metal supported on nanocarbon material.
[0065] In some embodiments, the present invention provides a method for preparing the CuZnAl catalyst modified by nano-carbon material and transition metal, the method comprising the following steps:
[0066] (1) using a carbon-containing gas to carbonize a transition metal raw material by chemical vapor deposition to prepare a nano-carbon-coated transition metal composite material;
[0067] (2) co-precipitating a solution containing three elements of Cu, Zn and Al to prepare an unmodified CuZnAl precipitation precursor;
[0068] Alternatively, a solution containing the two elements of Cu and Zn is subjected to a coprecipitation treatment, and pseudo-boehmite is added before or after the coprecipitation treatment to prepare an unmodified CuZnAl precipitation precursor;
[0069] Alternatively, a solution containing three elements of Cu, Zn and Al is co-precipitated with the nano-carbon-coated transition metal composite material obtained in step (1) to prepare a nano-carbon-coated transition metal-modified CuZnAl precipitation precursor;
[0070] (3) drying, calcining and shaping the unmodified CuZnAl precipitate precursor obtained in step (2) to obtain an unmodified CuZnAl catalyst;
[0071] Alternatively, the nanocarbon-coated transition metal composite material obtained in step (1) is added to the unmodified CuZnAl precipitate precursor obtained in step (2), followed by drying, calcining, and molding to obtain the CuZnAl catalyst modified with the nanocarbon material and the transition metal;
[0072] Alternatively, the nano-carbon-coated transition metal-modified CuZnAl precipitate precursor obtained in step (2) is dried, calcined, and formed to obtain the CuZnAl catalyst modified by the nano-carbon material and the transition metal;
[0073] (4) if no nano-carbon-coated transition metal composite material is added in steps (2) and (3), the unmodified CuZnAl catalyst obtained in step (3) is mixed evenly with the nano-carbon-coated transition metal composite material obtained in step (1), and the mixture is molded to obtain the CuZnAl catalyst modified with the nano-carbon material and the transition metal;
[0074] Alternatively, a soluble salt solution of transition metals Fe, Co, and Ni is added to the unmodified CuZnAl catalyst obtained in step (3), dried and calcined, carbonized in a carbon-containing atmosphere, and finally molded to obtain the CuZnAl catalyst modified with nano-carbon material and transition metal.
[0075] In a preferred embodiment, in step (1), the carbonization treatment of the transition metal by chemical vapor deposition using a carbon-containing mixed gas is to use a carbon-containing mixed gas to deposit carbon on the surface of the transition metal to generate the nano-carbon-coated transition metal composite material.
[0076] In a preferred embodiment, in step (1), the carbon-containing gas is a mixture of one or more carbon-containing gases selected from the group consisting of CO, methane, ethane, ethylene, acetylene, methanol vapor, ethanol vapor, benzene vapor, toluene vapor and CO2 and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar; preferably, the carbon-containing mixed gas is a mixture of one or more selected from the group consisting of CO, ethylene, methane and acetylene and one or more selected from the group consisting of H2, N2 and Ar.
[0077] In a preferred embodiment, in step (1), the concentration of the gas containing carbon in the mixed gas is 1-50 vol%, preferably 2-30 vol%, and more preferably 2-20 vol%.
[0078] In an exemplary embodiment, in step (1), the mixed gas is one of the following: 20 vol% CO-80 vol% N2, 2 vol% ethylene-98 vol% N2, 15v% methane-85 vol% N2, 2 vol% acetylene-98 vol% N2, 10 vol% CH4-90 vol% Ar, 3 vol% CO-1 vol% H2-96 vol% N2.
[0079] In a preferred embodiment, in step (1), the temperature of the carbonization treatment is 400-1100°C (preferably 650-950°C, 650-750°C or 750-950°C), the heating rate of the carbonization treatment is 1-30°C / min (preferably 1-5°C / min, 2-5°C / min or 1-2°C / min), and the time of the carbonization treatment is 0.1-10h (preferably 0.1-5h, 0.1-1h or 5-10h).
[0080] In a preferred embodiment, in step (1), the transition metal raw material is an oxide, nitrate, carbonate, acetate, oxalate, levulinate, citrate, laurate, metallocene compound, carbonyl metal compound and / or metal organic framework compound of Fe, Co and / or Ni.
[0081] In a preferred embodiment, in step (1), the transition metal in the nanocarbon-coated transition metal composite material is metal nanoparticles of Fe, Co and / or Ni; preferably, the size of the metal nanoparticles of Fe, Co and / or Ni is 2-50 nm; preferably, the metal nanoparticles of Fe, Co and / or Ni are derived from the reduction or pyrolysis of oxides, nitrates, carbonates, acetates, oxalates, levulinates, citrates, laurates, metallocene compounds, carbonyl metal compounds and / or metal organic framework compounds of Fe, Co and / or Ni as the transition metal raw materials in the carbon-containing gas or carbon-containing liquid; preferably, the oxides, nitrates, carbonates, acetates, oxalates, levulinates, citrates and / or laurates of Fe, Co and / or Ni can be supported on a carbon carrier or an acid-soluble oxide carrier; preferably, the acid The soluble oxide carrier is Al2O3, MgO, CaO and / or ZnO; preferably, the organic metal framework compound is 1,3,5-benzene trimecartrate iron, 1,3,5-benzene trimecartrate cobalt, 1,3,5-benzene trimecartrate nickel, ferrous terephthalate, cobalt terephthalate, nickel terephthalate, iron fumarate, cobalt fumarate, nickel fumarate, iron azobenzene tetracarboxylate, cobalt azobenzene tetracarboxylate, nickel azobenzene tetracarboxylate, amino-ferric terephthalate, amino Amino-cobalt terephthalate, amino-nickel terephthalate, 2,5-dihydroxyterephthalate iron, 2,5-dihydroxyterephthalate cobalt, 2,5-dihydroxyterephthalate nickel, 1,4-naphthalenedicarboxylic acid iron, 1,4-naphthalenedicarboxylic acid cobalt, 1,4-naphthalenedicarboxylic acid nickel, 1,5-naphthalenedicarboxylic acid iron, 1,5-naphthalenedicarboxylic acid cobalt, 1,5-naphthalenedicarboxylic acid nickel, 2,6-naphthalenedicarboxylic acid iron, 2,6-naphthalenedicarboxylic acid cobalt, 2,6-naphthalenedicarboxylic acid nickel, etc.
[0082] In a preferred embodiment, in step (1), the reactor for the carbonization treatment is a fixed fluidized bed reactor or a tubular reactor.
[0083] In a preferred embodiment, in step (1), when the reactor for carbonization treatment is a fixed fluidized bed reactor, the preparation of the nanocarbon-coated transition metal composite material comprises: placing the transition metal raw material in the fixed fluidized bed reactor, introducing the carbon-containing gas to fluidize the reaction bed of the fixed fluidized bed reactor, and heating to 400-1100°C at a heating rate of 1-30°C / min for carbonization for 5-10h.
[0084] In a preferred embodiment, in step (1), when the reactor for the carbonization treatment is a tubular reactor, the preparation of the nanocarbon-coated transition metal composite material includes: dissolving the transition metal raw material in methanol, ethanol, benzene and / or toluene, inputting it into the tubular reactor at a flow rate of 1-10 mL / h, maintaining the temperature of the constant temperature section of the tubular reactor at 400-1100°C; at the same time, introducing the carbon-containing gas at a flow rate of 1-10 L / min for carbonization for 5-10 hours.
[0085] In a preferred embodiment, in step (1), the preparation of the nanocarbon-coated transition metal composite material also includes: acid-treating the carbonized sample after the carbonization treatment to remove the transition metal or other impurity elements on the outer surface of the nanocarbon; preferably, the acid used in the acid treatment is an aqueous solution of hydrochloric acid, an aqueous solution of nitric acid, an aqueous solution of sulfuric acid, or a mixed aqueous solution thereof.
[0086] In a preferred embodiment, in step (2), the solution containing three elements of Cu, Zn and Al or the solution containing two elements of Cu and Zn is a soluble salt solution or a uniformly dispersed colloidal solution; the soluble salt solution is a solution containing one or more of the following soluble salts of Cu, Zn and / or Al: nitrate, chloride, sulfate and / or acetate, preferably, the soluble salt includes one or more of the following: copper nitrate, copper chloride, copper sulfate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, aluminum nitrate, aluminum sulfate, etc., but not limited thereto, further, the soluble salt is preferably its nitrate. The uniformly dispersed colloidal solution is a uniformly dispersed colloidal solution containing the soluble salt and colloid, preferably, the colloid is selected from AlOOH colloid, pseudo-boehmite colloid, Al2O3 colloid, but not limited thereto.
[0087] In a preferred embodiment, in step (2), the precipitant used in the coprecipitation treatment is selected from one or more of the following: ammonia water, sodium hydroxide, potassium hydroxide, ammonium bicarbonate, ammonium carbonate, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, sodium aluminate, potassium aluminate and the like, but not limited thereto; preferably, the precipitant is sodium bicarbonate and / or sodium carbonate.
[0088] In a preferred embodiment, in step (2), the solvent of the soluble salt solution or the uniformly dispersed colloidal solution is selected from a mixture of one or more of water, methanol, methylamine, dimethylamine, N,N-dimethylformamide, N-methylformamide, N-methylpyrrolidone, α-pyrrolidone, formamide, ethanol, ethylene glycol, ethyl ether, ethylamine, acetonitrile, acetamide, propanol, acetone, propionitrile, tetrahydrofuran, dioxane, butanol, pyridine, morpholine, quinoline, toluene, xylene, heptane, etc., but is not limited thereto; preferably, the water is deionized water.
[0089] In a preferred embodiment, in step (2), the metal molar concentration of the soluble salt solution is 0.1-10 mol / L, preferably 0.5-5 mol / L, most preferably 1-3 mol / L (eg 2-3 mol / L).
[0090] In a preferred embodiment, in step (2), the concentration of the colloid in the uniformly dispersed colloidal solution is 0.1 wt%-50 wt%, preferably 5 wt%-40 wt%, and most preferably 15 wt%-30 wt%.
[0091] In a preferred embodiment, in step (2), the pH value of the coprecipitation treatment is 3-11, preferably 6-9, and most preferably 7-8. The temperature of the coprecipitation treatment is 20-200°C, preferably 50-150°C, and most preferably 80-100°C (e.g. 85-100°C). The precipitation time of the precipitation treatment is 0.1-100h, preferably 0.5-24h, and most preferably 1-8h (e.g. 1.5-2h).
[0092] In a preferred embodiment, in step (2), the co-precipitation treatment comprises the following steps: heating the solution containing the three elements of Cu, Zn and Al to 20-200°C, and performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours to prepare an unmodified CuZnAl precipitation precursor.
[0093] In another preferred embodiment, in step (2), the co-precipitation treatment comprises the following steps: heating the solution containing the two elements Cu and Zn to 20-200°C, performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours, adding pseudo-boehmite, and preparing an unmodified CuZnAl precipitation precursor.
[0094] In another preferred embodiment, in step (2), the co-precipitation treatment comprises the following steps: adding pseudo-boehmite to the solution containing the two elements Cu and Zn, heating to 20-200°C, and performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours to prepare an unmodified CuZnAl precipitation precursor.
[0095] In another preferred embodiment, in step (2), the co-precipitation treatment comprises the following steps: mixing the solution containing the three elements of Cu, Zn and Al with the nano-carbon-coated transition metal composite material obtained in step (1), heating to 20-200°C, and performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100h to prepare a nano-carbon-coated transition metal modified CuZnAl precipitation precursor.
[0096] In a preferred embodiment, in step (2), after the co-current precipitation, the obtained precipitate is aged, filtered and washed. Preferably, the aging is carried out at the same temperature as the co-current precipitation, preferably, the aging time is 4-12 hours (e.g., 6-12 hours); preferably, the filtration and washing are carried out until the conductivity of the washing filtrate is 7.8-8.5 μs / cm (e.g., 8-8.5 μs / cm).
[0097] In a preferred embodiment, in step (3), the nanocarbon-coated transition metal composite material and water are added to the unmodified CuZnAl precipitation precursor to prepare a suspension with a solid content of 18-25wt% (e.g., 29-23wt%), and then the drying, calcination and molding are carried out to obtain the CuZnAl catalyst modified with nanocarbon material and transition metal.
[0098] In a preferred embodiment, in step (3), water is added to the nano-carbon-coated transition metal-modified CuZnAl precipitate precursor to prepare a suspension with a solid content of 18-25wt% (e.g., 29-23wt%), and then the suspension is dried, calcined, and formed to obtain the CuZnAl catalyst modified by the nano-carbon material and the transition metal.
[0099] In a preferred embodiment, in step (3), the unmodified CuZnAl precipitate precursor is directly dried, calcined, and formed to obtain an unmodified CuZnAl catalyst.
[0100] In a preferred embodiment, in step (3), water is added to the unmodified CuZnAl precipitation precursor to prepare a suspension with a solid content of 18-25wt% (e.g., 29-23wt%), and then drying, calcining and molding are performed to obtain an unmodified CuZnAl catalyst.
[0101] In a preferred embodiment, in step (3), the drying method is natural drying, sun drying, infrared drying, heating drying, vacuum drying, spray drying; the drying temperature is 20-250°C, preferably 80-150°C.
[0102] In a preferred embodiment, in step (3), the calcination atmosphere is air, nitrogen, argon or a mixture thereof; the calcination temperature is 300-700°C, preferably 400-600°C, most preferably 450-550°C; the calcination heating rate is 0.5-15°C / min, preferably 2-8°C / min; the calcination time is 2-12h, preferably 3-6h.
[0103] In a preferred embodiment, in step (4), the unmodified CuZnAl catalyst obtained in step (3) and the nano-carbon-coated transition metal composite material obtained in step (1) are uniformly mixed by mechanical mixing.
[0104] In a preferred embodiment, in step (4), a soluble salt solution of transition metals Fe, Co, and Ni is added to the unmodified CuZnAl catalyst obtained in step (3) by incipient wetness impregnation.
[0105] In a preferred embodiment, in step (4), the soluble salt solution of the transition metals Fe, Co and Ni is a soluble salt solution comprising one or more selected from the following: ferric nitrate, ferric chloride, ferrous chloride, ferrous sulfate, ferric acetylacetonate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt acetylacetonate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel acetylacetonate and the like, but not limited thereto; further, the soluble salt is preferably a nitrate thereof.
[0106] In a preferred embodiment, in step (4), the carbon-containing atmosphere is a mixture of one or more carbon-containing gases selected from the group consisting of CO, methane, ethane, ethylene, acetylene, methanol vapor, ethanol vapor, benzene vapor, toluene vapor and CO2 and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar; preferably, the carbon-containing mixed gas is a mixture of one or more selected from the group consisting of CO, ethylene, methane and acetylene and one or more selected from the group consisting of H2, N2 and Ar.
[0107] In a preferred embodiment, in step (4), the concentration of the gas containing carbon in the mixed gas is 1-50 vol%, preferably 2-30 vol%, and more preferably 2-20 vol%.
[0108] In an exemplary embodiment, in step (4), the mixed gas is one of the following: 20 vol% CO-80 vol% N2, 2 vol% ethylene-98 vol% N2, 15v% methane-85 vol% N2, 2 vol% acetylene-98 vol% N2, 10 vol% CH4-90 vol% Ar, 3 vol% CO-1 vol% H2-96 vol% N2.
[0109] In a preferred embodiment, in step (4), the temperature of the carbonization treatment is 400-700°C (preferably 550-650°C, 550-600°C or 600-650°C), the heating rate of the carbonization treatment is 5-30°C / min (preferably 6-10°C / min, 3-8°C / min or 8-10°C / min), and the time of the carbonization treatment is 0.05-10h (preferably 0.5-5h, 0.6-6h or 6-10h).
[0110] In a preferred embodiment, in steps (3) and (4), the molding method is spray molding, ball milling molding, tablet molding and extrusion molding.
[0111] In some preferred embodiments, the present invention further provides use of the CuZnAl catalyst modified by nano-carbon material and transition metal for preparing γ-butyrolactone by catalyzing maleic anhydride hydrogenation reaction.
[0112] In some preferred embodiments, the present invention further provides a method for preparing γ-butyrolactone by hydrogenating maleic anhydride over the CuZnAl catalyst modified by nanocarbon material and transition metal, the method comprising placing the CuZnAl catalyst modified by nanocarbon material and transition metal disclosed herein in a reactor, passing maleic anhydride raw material and hydrogen into the reactor to contact with the catalyst, and directly hydrogenating maleic anhydride to convert it into γ-butyrolactone by the catalyst.
[0113] In a preferred embodiment, the maleic anhydride raw material includes one or more selected from the following: maleic anhydride, succinic anhydride, dimethyl maleate, diethyl maleate, dibutyl maleate, dimethyl fumarate, diethyl fumarate, dibutyl fumarate, dimethyl succinate, diethyl succinate, dibutyl succinate, or derivatives thereof.
[0114] In a preferred embodiment, the pressure of the maleic anhydride hydrogenation reaction is 0.1-10.0 MPa, preferably 0.5-5 MPa, more preferably 0.8-2.0 MPa; the temperature of the maleic anhydride hydrogenation reaction is 150-350°C, preferably 200-300°C, more preferably 260-280°C; the liquid hourly space velocity (weight space velocity) of the maleic anhydride raw material is 0.1-10 g / g-Cat. / h, preferably 0.5-5 g / g-Cat. / h, more preferably 1-3 g / g-Cat. / h; the molar ratio of H2 to maleic anhydride raw material in the maleic anhydride hydrogenation reaction is 4.5-1000, preferably 10-100, more preferably 20-50; the H2 circulation ratio of the maleic anhydride hydrogenation reaction is 2-100 (v / v), preferably 5-50, more preferably 8-12.
[0115] The exemplary scheme described in the present invention has the following characteristics: the catalyst preparation method is simple, the raw materials are cheap, the production cost is low, and the repeatability is good; the catalyst disclosed in the present invention has a large specific surface area (50-450m 2 / g), high mechanical strength (wear index is 1-2.0%·h -1 ), high thermal stability and good metal active phase sintering resistance; when the transition metal modified catalyst disclosed in the present invention is used for maleic anhydride hydrogenation reaction, the conversion rate of maleic anhydride is greater than 99%, the selectivity of γ-butyrolactone is as high as 93%, and the space-time yield can reach 3h -1 And a single operation cycle exceeds 3000h.
[0116] Specifically, the present invention can be carried out through the scheme shown in the following paragraphs:
[0117] [1]. A CuZnAl catalyst modified by nanocarbon material and transition metal, the catalyst contains CuO, ZnO, Al2O3, transition metal and nanocarbon material, wherein the transition metal is at least one of Fe, Co and Ni; the nanocarbon material is at least one of fullerene, carbon nanocage, single-walled nanotube and multi-walled carbon nanotube; the transition metal is encapsulated in the nanocarbon material structure.
[0118] [2] The catalyst according to paragraph [1], wherein the catalyst consists of CuO, ZnO, Al2O3, transition metal and nanocarbon material.
[0119] [3] The catalyst according to paragraph [1] or [2], wherein, relative to the total mass of the catalyst, the mass content of CuO is 15-70wt%; the mass content of ZnO is 5-60wt%; the mass content of Al2O3 is 2-30wt%; the mass content of the transition metal is 0.001-5wt%; and the mass content of the nanocarbon material is 0.5-20wt%.
[0120] [4] The catalyst according to paragraph [1] or [2], wherein, relative to the total mass of the catalyst, the mass content of CuO is 25-60wt%; the mass content of ZnO is 15-50wt%; the mass content of Al2O3 is 5-20wt%; the mass content of the transition metal is 0.01-2wt%; and the mass content of the nanocarbon material is 0.1-10wt%.
[0121] [5] The catalyst according to paragraph [1] or [2], wherein, relative to the total mass of the catalyst, the mass content of CuO is 40-50wt%; the mass content of ZnO is 30-40wt%; the mass content of Al2O3 is 8-15wt%; the mass content of the transition metal is 0.1-1wt%; and the mass content of the nanocarbon material is 1-5wt%.
[0122] [6]. A catalyst according to any one of paragraphs [1] to [5], wherein the transition metal is encapsulated in the nanocarbon material structure to form one or more structures selected from the following structures: Fe@fullerene, Co@fullerene, Ni@fullerene, Fe@carbon nanocage, Co@carbon nanocage, Ni@carbon nanocage, Fe@single-walled carbon nanotube, Co@single-walled carbon nanotube, Ni@single-walled carbon nanotube, Fe@multi-walled carbon nanotube, Co@multi-walled carbon nanotube, Ni@multi-walled carbon nanotube.
[0123] [7] A method for preparing a catalyst according to any one of paragraphs [1] to [6], the method comprising the following steps:
[0124] (1) using a carbon-containing gas to carbonize a transition metal raw material by chemical vapor deposition to prepare a nano-carbon-coated transition metal composite material;
[0125] (2) co-precipitating a solution containing three elements of Cu, Zn and Al to prepare an unmodified CuZnAl precipitation precursor;
[0126] Alternatively, a solution containing the two elements of Cu and Zn is subjected to a coprecipitation treatment, and pseudo-boehmite is added before or after the coprecipitation treatment to prepare an unmodified CuZnAl precipitation precursor;
[0127] (3) drying, calcining and shaping the unmodified CuZnAl precipitate precursor obtained in step (2) to obtain an unmodified CuZnAl catalyst;
[0128] Alternatively, the nanocarbon-coated transition metal composite material obtained in step (1) is added to the unmodified CuZnAl precipitate precursor obtained in step (2), followed by drying, calcining, and molding to obtain the CuZnAl catalyst modified with the nanocarbon material and the transition metal;
[0129] (4) if the nano-carbon-coated transition metal composite material is not added in step (3), the unmodified CuZnAl catalyst obtained in step (3) is mixed evenly with the nano-carbon-coated transition metal composite material obtained in step (1), and the mixture is molded to obtain the CuZnAl catalyst modified with the nano-carbon material and the transition metal;
[0130] Alternatively, a soluble salt solution of transition metals Fe, Co, and Ni is added to the unmodified CuZnAl catalyst obtained in step (3), dried and calcined, carbonized in a carbon-containing atmosphere, and finally molded to obtain the CuZnAl catalyst modified with nano-carbon material and transition metal.
[0131] [8] A method for preparing a catalyst according to any one of paragraphs [1] to [6], the method comprising the following steps:
[0132] (1) using a carbon-containing gas to carbonize a transition metal raw material by chemical vapor deposition to prepare a nano-carbon-coated transition metal composite material;
[0133] (2) co-precipitating a solution containing three elements of Cu, Zn and Al with the nano-carbon-coated transition metal composite material obtained in step (1) to prepare a nano-carbon-coated transition metal modified CuZnAl precipitation precursor;
[0134] (3) Drying, calcining and molding the nano-carbon-coated transition metal-modified CuZnAl precipitate precursor obtained in step (2) to obtain the CuZnAl catalyst modified by the nano-carbon material and the transition metal.
[0135] [9]. According to the method described in paragraph [7] or [8], in step (1), the carbon-containing gas is a mixture of one or more carbon-containing gases selected from the group consisting of CO, methane, ethane, ethylene, acetylene, methanol vapor, ethanol vapor, benzene vapor, toluene vapor and CO2 and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar.
[0136]
[10] . According to the method described in paragraph [9], in step (1), the carbon-containing gas is a mixture of one or more carbon-containing gases selected from the group consisting of CO, ethylene, methane and acetylene and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar.
[0137]
[11] . According to the method described in paragraph [9] or
[10] , in step (1), the concentration of the gas containing carbon in the mixed gas is 1-50 vol%.
[0138]
[12] According to the method described in any one of paragraphs [7] to
[11] , in step (1), the temperature of the carbonization treatment is 400-1100°C, the heating rate of the carbonization treatment is 1-30°C / min, and the time of the carbonization treatment is 0.1-10h.
[0139]
[13] . According to the method described in any one of paragraphs [7] to
[12] , in step (1), the transition metal raw material is an oxide, nitrate, carbonate, acetate, oxalate, levulinate, citrate, laurate, metallocene compound, carbonyl metal compound and / or metal organic framework compound of Fe, Co and / or Ni.
[0140]
[14] . According to the method described in any one of paragraphs [7]-
[13] , in step (1), the transition metal in the nanocarbon-coated transition metal composite material is metal nanoparticles of Fe, Co and / or Ni.
[0141]
[15] . According to the method described in paragraph
[14] , in step (1), the size of the Fe, Co and / or Ni metal nanoparticles is 2-50 nm.
[0142]
[16] According to the method described in paragraph
[14] or
[15] , in step (1), the transition metal raw material is supported on a carbon support or an acid-soluble oxide support.
[0143]
[17] According to the method described in paragraph
[16] , in step (1), the acid-soluble oxide carrier is Al2O3, MgO, CaO and / or ZnO.
[0144]
[18] . According to the method described in paragraph
[13] , in step (1), the organic metal framework compound is selected from one or more of the following compounds: 1,3,5-benzene trimecartrate iron, 1,3,5-benzene trimecartrate cobalt, 1,3,5-benzene trimecartrate nickel, ferrous terephthalate, cobalt terephthalate, nickel terephthalate, ferrous fumarate, cobalt fumarate, nickel fumarate, ferric azobenzene tetracarboxylate, cobalt azobenzene tetracarboxylate, nickel azobenzene tetracarboxylate, amino-terephthalate Iron formate, amino-cobalt terephthalate, amino-nickel terephthalate, iron 2,5-dihydroxyterephthalate, cobalt 2,5-dihydroxyterephthalate, nickel 2,5-dihydroxyterephthalate, iron 1,4-naphthalenedicarboxylate, cobalt 1,4-naphthalenedicarboxylate, nickel 1,4-naphthalenedicarboxylate, iron 1,5-naphthalenedicarboxylate, cobalt 1,5-naphthalenedicarboxylate, nickel 1,5-naphthalenedicarboxylate, iron 2,6-naphthalenedicarboxylate, cobalt 2,6-naphthalenedicarboxylate, nickel 2,6-naphthalenedicarboxylate.
[0145]
[19] . According to the method described in any one of paragraphs [7] to
[18] , in step (1), the reactor for carbonization treatment is a fixed fluidized bed reactor or a tubular reactor.
[0146]
[20] . According to the method described in paragraph
[19] , in step (1), when the reactor for carbonization treatment is a fixed fluidized bed reactor, the preparation of the nanocarbon-coated transition metal composite material includes: placing the transition metal raw material in the fixed fluidized bed reactor, introducing the carbon-containing gas to make the reaction bed of the fixed fluidized bed reactor in a fluidized state, and heating to 400-1100°C at a heating rate of 1-30°C / min for carbonization for 5-10h.
[0147]
[21] . According to the method described in paragraph
[19] , in step (1), when the reactor for the carbonization treatment is a tubular reactor, the preparation of the nanocarbon-coated transition metal composite material includes: dissolving the transition metal raw material in methanol, ethanol, benzene and / or toluene, inputting it into the tubular reactor at a flow rate of 1-10 mL / h, and maintaining the temperature of the constant temperature section of the tubular reactor at 400-1100°C; at the same time, introducing the carbon-containing gas at a flow rate of 1-10 L / min for carbonization for 5-10 hours.
[0148]
[22] . According to the method described in any one of paragraphs [7] to
[21] , in step (1), the preparation of the nanocarbon-coated transition metal composite material also includes: subjecting the carbonized sample after the carbonization treatment to an acid treatment; preferably, the acid used in the acid treatment is an aqueous hydrochloric acid solution, an aqueous nitric acid solution, an aqueous sulfuric acid solution or a mixed aqueous solution thereof.
[0149]
[23] . According to the method described in any one of paragraphs [7] to
[22] , in step (2), the solution containing three elements of Cu, Zn and Al or the solution containing two elements of Cu and Zn is a soluble salt solution or a uniformly dispersed colloidal solution.
[0150]
[24] According to the method described in paragraph
[23] , in step (2), the soluble salt solution is a solution containing one or more of the following soluble salts of Cu, Zn and / or Al: nitrate, chloride, sulfate and / or acetate.
[0151]
[25] . According to the method described in paragraph
[24] , in step (2), the soluble salt is selected from one or more of the following: copper nitrate, copper chloride, copper sulfate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, aluminum nitrate, and aluminum sulfate.
[0152]
[26] . According to the method described in paragraph
[23] , in step (2), the uniformly dispersed colloidal solution is a uniformly dispersed colloidal solution containing a soluble salt and a colloid; preferably, the colloid is selected from one or more of AlOOH colloid, pseudo-boehmite colloid, and Al2O3 colloid; and the soluble salt is selected from one or more of the following: copper nitrate, copper chloride, copper sulfate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, aluminum nitrate, and aluminum sulfate.
[0153]
[27] . According to the method described in any one of paragraphs [7] to
[26] , in step (2), the precipitant used in the co-precipitation treatment is selected from one or more of the following: ammonia water, sodium hydroxide, potassium hydroxide, ammonium bicarbonate, ammonium carbonate, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, sodium aluminate, potassium aluminate.
[0154]
[28] . According to the method described in any one of paragraphs
[23] to
[26] , in step (2), the solvent of the soluble salt solution or the uniformly dispersed colloidal solution is selected from a mixture of one or more of water, methanol, methylamine, dimethylamine, N,N-dimethylformamide, N-methylformamide, N-methylpyrrolidone, α-pyrrolidone, formamide, ethanol, ethylene glycol, ethyl ether, ethylamine, acetonitrile, acetamide, propanol, acetone, propionitrile, tetrahydrofuran, dioxane, butanol, pyridine, morpholine, quinoline, toluene, xylene, and heptane.
[0155]
[29] According to the method described in any one of paragraphs
[23] to
[26] , in step (2), the metal molar concentration of the soluble salt solution is 0.1-10 mol / L.
[0156]
[30] . According to the method described in any one of paragraphs
[23] to
[26] , in step (2), the concentration of the colloid in the uniformly dispersed colloidal solution is 0.1 wt% to 50 wt%.
[0157]
[31] . According to the method described in any one of paragraphs [7] to
[30] , in step (2), the pH value of the co-precipitation treatment is 3-11; the temperature of the co-precipitation treatment is 20-200°C; and the precipitation time of the precipitation treatment is 0.1-100h.
[0158]
[32] According to the method described in any one of paragraphs
[27] to
[31] , in step (2), the co-precipitation treatment comprises the following steps: heating the solution containing the three elements of Cu, Zn and Al to 20-200°C, and performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours to prepare an unmodified CuZnAl precipitation precursor.
[0159]
[33] . According to the method described in any one of paragraphs
[27] to
[31] , in step (2), the co-precipitation treatment comprises the following steps: heating the solution containing the two elements Cu and Zn to 20-200°C, performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours, adding pseudo-boehmite, and preparing an unmodified CuZnAl precipitation precursor.
[0160]
[34] . According to the method described in any one of paragraphs
[27] to
[31] , in step (2), the co-precipitation treatment comprises the following steps: adding pseudo-boehmite to the solution containing the two elements Cu and Zn, heating to 20-200°C, and co-precipitating with the precipitant at a pH value of 3-11 for 0.1-100 hours to prepare an unmodified CuZnAl precipitation precursor.
[0161]
[35] . According to the method described in any one of paragraphs
[27] -31], in step (2), the co-precipitation treatment comprises the following steps: mixing the solution containing the three elements of Cu, Zn and Al with the nano-carbon-coated transition metal composite material obtained in step (1), heating to 20-200°C, and performing co-current precipitation with the precipitant at a pH value of 3-11 for 0.1-100 hours to prepare a nano-carbon-coated transition metal modified CuZnAl precipitation precursor.
[0162]
[36] . According to the method described in any one of paragraphs
[32] to
[35] , in step (2), after the co-current sedimentation, the obtained precipitate is aged, filtered and washed; preferably, the aging is carried out at the same temperature as the co-current sedimentation; preferably, the aging time is 4-12h; preferably, the filtration and washing are carried out until the conductivity of the washing filtrate is 7.8-8.5μs / cm.
[0163]
[37] . According to the method described in any one of paragraphs [7] to
[36] , in step (3), the nanocarbon-coated transition metal composite material and water are added to the unmodified CuZnAl precipitation precursor to prepare a suspension, and then the suspension is dried, calcined and formed to obtain the CuZnAl catalyst modified with the nanocarbon material and the transition metal.
[0164]
[38] . According to the method described in any one of paragraphs [7] to
[36] , in step (3), water is added to the nanocarbon-coated transition metal-modified CuZnAl precipitate precursor to prepare a suspension, and then drying, calcining and molding are performed to obtain the CuZnAl catalyst modified by nanocarbon material and transition metal.
[0165]
[39] According to the method described in paragraph
[37] or
[38] , in step (3), the solid content of the suspension is 18-25wt%.
[0166]
[40] According to the method described in any one of paragraphs [7] to
[36] , in step (3), the unmodified CuZnAl precipitate precursor is directly dried, calcined and formed to obtain an unmodified CuZnAl catalyst.
[0167]
[41] . According to the method described in any one of paragraphs [7] to
[36] , in step (3), water is added to the unmodified CuZnAl precipitate precursor to prepare a suspension, and then drying, calcining and molding are performed to obtain an unmodified CuZnAl catalyst.
[0168]
[42] According to the method described in paragraph
[41] , in step (3), the solid content of the suspension is 18-25wt%.
[0169]
[43] . According to the method described in any one of paragraphs [7] to
[42] , in step (3), the drying method is natural drying, sun drying, infrared drying, heating drying, vacuum drying, or spray drying; the drying temperature is 20-250°C.
[0170]
[44] . According to the method described in any one of paragraphs [7] to
[43] , in step (3), the calcination atmosphere is air, nitrogen, argon or a mixture thereof; the calcination temperature is 300-700°C; the calcination heating rate is 0.5-15°C / min; and the calcination time is 2-12h.
[0171]
[45] . According to the method described in any one of paragraphs [7] to
[44] , in step (4), the soluble salt solution of transition metals Fe, Co and Ni is a soluble salt solution comprising one or more selected from the following: ferric nitrate, ferric chloride, ferrous chloride, ferrous sulfate, ferric acetylacetonate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt acetylacetonate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate and nickel acetylacetonate.
[0172]
[46] . According to the method described in any one of paragraphs [7] to
[45] , in step (4), the carbon-containing atmosphere is a mixture of one or more carbon-containing gases selected from the group consisting of CO, methane, ethane, ethylene, acetylene, methanol vapor, ethanol vapor, benzene vapor, toluene vapor and CO2 and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar.
[0173]
[47] . According to the method described in paragraph
[46] , in step (4), the carbon-containing atmosphere is a mixture of one or more carbon-containing gases selected from the group consisting of CO, ethylene, methane and acetylene and one or more non-carbon-containing gases selected from the group consisting of H2, N2 and Ar.
[0174]
[48] . According to the method described in paragraph
[46] , in step (4), the concentration of the gas containing carbon in the mixed gas is 1-50 vol%.
[0175]
[49] . According to the method described in any one of paragraphs [7] to
[48] , in step (4), the temperature of the carbonization treatment is 400-700°C, the heating rate of the carbonization treatment is 5-30°C / min, and the time of the carbonization treatment is 0.05-10h.
[0176]
[50] . According to the method described in any one of paragraphs [7]-
[49] , in step (3) and step (4), the forming is spray forming, ball milling, tableting and / or extrusion forming.
[0177]
[51] . Use of the CuZnAl catalyst modified with nanocarbon material and transition metal according to any one of paragraphs [1] to [6] or the CuZnAl catalyst modified with nanocarbon material and transition metal prepared according to the method described in any one of paragraphs [7] to
[50] for preparing γ-butyrolactone by catalyzing maleic anhydride hydrogenation reaction.
[0178]
[52] . A method for preparing γ-butyrolactone by hydrogenation of maleic anhydride, the method comprising placing a CuZnAl catalyst modified with nanocarbon material and transition metal according to any one of paragraphs [1] to [6] or a CuZnAl catalyst modified with nanocarbon material and transition metal prepared according to any one of paragraphs [7] to
[50] in a reactor, passing maleic anhydride raw material and hydrogen into the reactor to contact the catalyst, and directly hydrogenating maleic anhydride to γ-butyrolactone by the catalyst.
[0179]
[53] . The method according to paragraph
[52] , wherein the maleic anhydride raw material comprises one or more selected from the following: maleic anhydride, succinic anhydride, dimethyl maleate, diethyl maleate, dibutyl maleate, dimethyl fumarate, diethyl fumarate, dibutyl fumarate, dimethyl succinate, diethyl succinate, dibutyl succinate, or derivatives thereof.
[0180]
[54] . The method according to paragraph
[52] or
[53] , wherein the pressure of the maleic anhydride hydrogenation reaction is 0.1-10.0 MPa; the temperature of the maleic anhydride hydrogenation reaction is 150-350°C; the liquid hourly space velocity of the maleic anhydride raw material is above 0.5 g / g-Cat. / h; the molar ratio of H2 to maleic anhydride raw material in the maleic anhydride hydrogenation reaction is 4.5-1000; and the H2 circulation ratio in the maleic anhydride hydrogenation reaction is 2-100 (v / v).
[0181] The present invention is not limited to the preferred embodiments and applications described above, and those skilled in the art may modify these embodiments and applications without departing from the purpose of the present invention.
[0182] Example
[0183] The following examples are used to illustrate the present invention in more detail, but the present invention is not limited thereto.
[0184] In the following examples, the elemental composition of the samples was characterized by inductively coupled plasma-atomic emission spectrometry (ICP-OES). After high temperature roasting, the samples were acid-digested and prepared into a solution of a certain concentration, and an appropriate amount of the solution was taken to compare with the standard curve to obtain the content of the corresponding element.
[0185] In the following examples, the X-ray powder diffraction patterns of the catalyst samples were measured using an X-ray diffractometer with a Co target Kα light source. The tube voltage was 40 kV, the tube current was 35 mA, the scanning range was 10-90°, the step length was 0.04°, and the dwell time was 0.4 s.
[0186] In the following examples, the morphology of the catalysts was tested by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).
[0187] In the following examples, the catalyst wear resistance test was carried out in an air jet abrasion tester. The method is as follows: first, the sample is sieved to remove fine powder below 200 mesh, 50g of the sieved sample is weighed and spread on a surface dish, and the surface dish is placed in a dryer with a saturated calcium chloride solution at the bottom for humidification to reduce the static electricity generated in subsequent tests. s The sample is added into the air jet wear tube, and a collection well with a weight of m0 is inserted into the top. Air with a humidity of 20% is introduced at a rate of 100 ml / min. After 5 hours, the collection well is removed and weighed, which is recorded as m1. The catalyst wear rate is calculated as follows:
[0188] Wear rate = (m1-m0) / m s ×100%
[0189] In the following examples, the acidity of the liquid product is determined by the acid-base neutralization method: first, a 0.1M solution is prepared with anhydrous sodium carbonate, then 1.0g of the sample is accurately weighed, 10g of deionized water and 2d of phenolphthalein indicator are added respectively, and the solution is titrated with sodium carbonate solution. The color of the solution changes from colorless to pink, and the titration volume (V / ml) is recorded. Then, the acidity of the sample = 0.49*V, %, wherein 0.49 is the conversion coefficient of maleic anhydride concentration to sodium carbonate volume, and this value coefficient is obtained by calibrating the curve with different maleic anhydride concentrations.
[0190] Example 1
[0191] Weigh 100g of a metal organic framework compound, ferrous terephthalate (Fe-MIL-100), and place it in a fixed fluidized bed reactor. Pass 2% acetylene-98% N2 carbon-containing gas to make the reaction bed in a fluidized state. Heat to 650°C at a heating rate of 1°C / min and carbonize for 5 hours. Take out the carbonized sample and reflux it in a 2M nitric acid aqueous solution. Then wash it with deionized water to obtain a carbon-coated Fe nanoparticle composite material, wherein the size of the Fe nanoparticles is 10-50nm; its elemental mass composition is: Fe / C=1.3 / 98.7, marked as C-1.
[0192] Example 2
[0193] Weigh 100 g of CoO / Al2O3 powdered catalyst with a cobalt loading of 20 wt.%, place it in a fixed fluidized bed reactor, introduce 10% CH4-90% Ar carbon-containing gas to make the reaction bed in a fluidized state, heat to 750°C at a heating rate of 2°C / min and carbonize for 10 h, take out the carbonized sample, place it in 3M hydrochloric acid aqueous solution for reflux treatment, and then wash it with deionized water to obtain a carbon-coated Co nanoparticle composite material, wherein the size of the Co nanoparticles is 5-10 nm; its elemental mass composition is: Co / C=0.4 / 99.6, marked as C-2.
[0194] Example 3
[0195] 10 ml of nickel tetracarbonyl was dissolved in 200 ml of toluene, and then introduced into a Φ80×1700 mm tubular reactor (the length of the constant temperature section was 800 mm) at a flow rate of 10 ml / h by a liquid phase pump, and the temperature of the constant temperature section of the reactor was maintained at 950°C. At the same time, 3% CO-1% H2-96% N2 carbon-containing gas was introduced at a flow rate of 1 L / min for carbonization for 0.1 h to prepare a carbon-coated Ni metal composite material, and the carbonized sample was taken out and placed in a 1M sulfuric acid aqueous solution for reflux treatment, and then washed with deionized water to obtain a carbon-coated Ni nanoparticle composite material, wherein the size of the nickel nanoparticles was 10-30 nm; its elemental mass composition was: Ni / C=0.6 / 99.4, marked as C-3.
[0196] Example 4
[0197] Weigh 564.8g of copper nitrate trihydrate, 679.9g of zinc nitrate hexahydrate and 116.8g of aluminum nitrate hydrate, dissolve in an appropriate amount of deionized water to prepare a CuZnAl solution with a metal molar concentration of 3.0M, and heat to 75°C; co-precipitate the heated CuZnAl solution with a 2M NaHCO3 solution, and adjust the pH value to 8; the precipitation time is 1h. After the precipitation is completed, maintain 75°C for stirring and aging for 6h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. An appropriate amount of deionized water was added to the filtered precipitate, and a uniform suspension was formed by shear dispersion with a solid content of 22 wt%. The product was spray dried at 160 °C, calcined to 450 °C in a muffle furnace at a heating rate of 2 °C / min and maintained for 6 hours, and extruded to obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3=46.5 / 46.5 / 7.0, marked as C-4.
[0198] Reaction test: 100g of the above catalyst C-4 was taken, placed in a reactor, and reduced with 0.2MPa pure H2 at 260°C for 5h. After the reduction was completed, the H2 pressure was raised to 1.0MPa, and the H2 space velocity was adjusted to 120000ml / g-cat / h. At the same time, maleic anhydride was fed by a liquid phase pump, and the liquid hourly space velocity of maleic anhydride was 0.5g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 30, and the H2 circulation ratio was 10. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0199] Example 5
[0200] Weigh 564.8g of copper nitrate trihydrate, 679.9g of zinc nitrate hexahydrate and 116.8g of aluminum nitrate hydrate, dissolve in an appropriate amount of deionized water to prepare a CuZnAl solution with a metal molar concentration of 3.0M, and heat to 75°C; co-precipitate the heated CuZnAl solution with a 2M NaHCO3 solution, and adjust the pH value to 8; the precipitation time is 1h. After the precipitation is completed, maintain 75°C for stirring and aging for 6h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. To the filtered precipitate, add 5 g of the C-1 sample prepared in Material Preparation Example 1 and an appropriate amount of deionized water, and use shear dispersion to form a uniform suspension with a solid content of 22 wt%; spray dry at 160°C, calcine to 450°C in a nitrogen atmosphere at a heating rate of 2°C / min and maintain for 6 hours, extrude into strips, and obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Fe / C=45.9 / 46.0 / 6.9 / 0.02 / 1.2, marked as C-5.
[0201] Reaction test: 100g of the above catalyst C-5 was taken, placed in a reactor, and reduced with 0.2MPa pure H2 at 260°C for 5h. After the reduction was completed, the H2 pressure was raised to 1.0MPa, and the H2 space velocity was adjusted to 120000ml / g-cat / h. At the same time, maleic anhydride was fed by a liquid phase pump, and the liquid hourly space velocity of maleic anhydride was 0.5g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 50, and the H2 circulation ratio was 9. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0202] Example 6
[0203] 564.8 g of copper nitrate trihydrate, 679.9 g of zinc nitrate hexahydrate and 116.8 g of hydrated aluminum nitrate were weighed and dissolved in an appropriate amount of deionized water to prepare a CuZnAl solution with a metal molar concentration of 3.0 M. Then 7 g of the C-2 sample prepared in Example 2 was added, stirred and mixed to form a uniform suspension, and heated to 75°C; the heated suspension was co-precipitated with a 2M NaHCO3 solution, and the pH value was adjusted to 8; the precipitation time was 2 h. After the precipitation was completed, the mixture was maintained at 75°C for stirring and aging for 6 h; then the precipitate was filtered and washed until the conductivity of the washing filtrate was 8 μs / cm. An appropriate amount of deionized water was added to the filtered precipitate, and a uniform suspension was formed by shear dispersion with a solid content of 22 wt%. The product was spray dried at 120 °C, calcined to 500 °C in a muffle furnace at a heating rate of 2 °C / min and maintained for 5 hours, and extruded to obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Co / C=45.7 / 45.8 / 6.9 / 0.006 / 1.6, marked as C-6.
[0204] Reaction test: 100g of the above catalyst C-6 was taken, placed in a reactor, and reduced with 0.2MPa pure H2 at 280°C for 5h. After the reduction was completed, the temperature was lowered to 250°C, the H2 pressure was raised to 1.0MPa, and the H2 space velocity was adjusted to 120000ml / g-cat / h. At the same time, maleic anhydride was fed by a liquid phase pump, and the liquid hourly space velocity of maleic anhydride was 1.5g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 50, and the H2 circulation ratio was 11. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0205] Example 7
[0206] Weigh 509.3g of copper nitrate trihydrate, 395.9g of zinc nitrate hexahydrate and 70.2g of aluminum nitrate, dissolve and disperse in deionized water to prepare a CuZnAl solution with a metal molar concentration of 2.0M, and heat to 85°C; co-precipitate the heated CuZnAl solution with 1M Na2CO3 solution, and adjust the pH value to 7; the precipitation time is 1h. After the precipitation is completed, maintain 85°C for stirring and aging for 4h; then filter and wash the precipitate until the conductivity of the washing filtrate is 9μs / cm. To the filtered precipitate, add 10 g of the C-3 sample prepared in Material Preparation Example 3 and an appropriate amount of deionized water, and use shear dispersion to form a uniform suspension with a solid content of 23 wt%; spray dry at 150°C, calcine to 400°C in a nitrogen atmosphere at a heating rate of 1°C / min and maintain for 4 hours, extrude into strips, and obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Ni / C=55.4 / 35.7 / 5.6 / 0.02 / 3.3, marked as C-7.
[0207] Reaction test: 100g of the above catalyst C-7 was taken, placed in a reactor, and reduced with 0.2MPa pure H2 at 300℃ for 5h. After the reduction was completed, the temperature was lowered to 260℃, the H2 pressure was raised to 2.0MPa, and the H2 space velocity was adjusted to 50000ml / g-cat / h. The reaction raw material was dibutyl maleate, and a liquid phase pump was used for feeding. The liquid hourly space velocity of dibutyl maleate was 2.0g / g-cat / h. The molar ratio of H2 to raw material maleic anhydride in the maleic anhydride hydrogenation reaction was 60, and the H2 circulation ratio was 8. During the reaction, the composition of the reaction tail gas and liquid phase products was analyzed by gas chromatography every 12h, and the acidity of the liquid phase products was measured, which was used to calculate the conversion rate and product selectivity of dibutyl maleate in the reaction. The reaction results are listed in Table 1.
[0208] Example 8
[0209] Weigh 564.8g of copper nitrate trihydrate and 624.7g of zinc nitrate hexahydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZn solution with a metal molar concentration of 2.0M, and heat it to 70°C; precipitate the heated CuZn solution with a 2M NaHCO3 solution in parallel, and adjust the pH value to 7; the precipitation time is 1.5h. After the precipitation is completed, add 47.6g of pseudo-boehmite (containing 75wt% of dry Al2O3) to the precipitation reactor and maintain 70°C for stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. The filtered precipitate is dried at 120°C, and calcined to 450°C in a muffle furnace at a heating rate of 2°C / min and maintained for 6 hours to obtain a CuZnAl precursor. Weigh 10 g of the C-1 sample prepared in Material Preparation Example 1 and mix it evenly with 300 g of CuZnAl precursor, and extrude it into strips to obtain a Φ5×5 mm cylindrical catalyst with the elemental mass composition of CuO / ZnO / Al2O3 / Fe / C=46.2 / 42.4 / 8.9 / 0.08 / 2.4, marked as C-8.
[0210] Reaction test: 100g of the above catalyst C-8 was taken, placed in a reactor, and reduced with 0.2MPa pure H2 at 320℃ for 5h. After the reduction was completed, the temperature was lowered to 300℃, the H2 pressure was raised to 4.0MPa, the H2 space velocity was adjusted to 48000ml / g-cat / h, the reaction raw material was 55% maleic anhydride / 45% γ-butyrolactone solution, and the liquid phase pump was used for feeding. The liquid hourly space velocity of maleic anhydride was 3.0g / g-cat / h, the molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 40, and the H2 circulation ratio was 10. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 2.
[0211] Example 9
[0212] Weigh 1037.8g of copper nitrate trihydrate and 420.3g of zinc nitrate hexahydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZn solution with a metal molar concentration of 2.0M, then add 48.9g of pseudo-boehmite (containing 75wt% of dry Al2O3), stir to form a uniform suspension, and heat to 70°C; the heated CuZnAl mixed solution is precipitated with 1.5M Na2CO3 solution, and the pH value is adjusted to 7; the precipitation time is 2h, and after the precipitation is completed, maintain 70°C stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. The filtered precipitate is dried at 120°C, and calcined to 550°C in a muffle furnace at a heating rate of 2°C / min and maintained for 3 hours to obtain a CuZnAl precursor. Weigh 6 g of the C-2 sample prepared in Material Preparation Example 2 and mix it evenly with 455 g of CuZnAl precursor, and extrude it into strips to obtain a Φ5×5 mm cylindrical modified CuZnAl catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Co / C=68.3 / 23.1 / 7.3 / 0.005 / 1.3, marked as C-9.
[0213] Reaction test: Take 5g of the above catalyst C-9, place it in a reactor, and reduce it with 0.2MPa pure H2 at 280℃ for 5h. After the reduction is completed, the H2 pressure is raised to 2.0MPa, and the H2 space velocity is adjusted to 32000ml / g-cat / h. The reaction raw material is maleic anhydride, and a liquid phase pump is used for feeding. The liquid hourly space velocity of maleic anhydride is 2.0g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride is 50, and the H2 circulation ratio is 12. During the reaction, the composition of the reaction tail gas and the liquid phase product is analyzed by gas chromatography every 12h, and the acidity of the liquid phase product is measured, which is used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0214] Example 10
[0215] Weigh 2017.4g of copper nitrate trihydrate, 2305.1g of zinc nitrate hexahydrate and 576.7g of aluminum nitrate hydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZnAl solution with a metal molar concentration of 3.0M, and heat it to 85°C; precipitate the heated CuZnAl solution with a 1.5M Na2CO3 solution and adjust the pH value to 7; the precipitation time is 1.5h, and after the precipitation is completed, maintain 85°C for stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. Add an appropriate amount of deionized water to the filtered precipitate, and use shear dispersion to form a uniform suspension with a solid content of 19wt%; spray dry at 150°C, and roast to 500°C in a muffle furnace at a heating rate of 2°C / min and keep it for 5 hours to obtain a CuZnAl precursor. Weigh 2 g of the C-3 sample prepared in Material Preparation Example 3 and mix it evenly with 300 g of CuZnAl precursor, and extrude it into strips to obtain a Φ5×5 mm cylindrical catalyst with the elemental mass composition of CuO / ZnO / Al2O3 / Ni / C=46.0 / 43.8 / 9.6 / 0.003 / 0.6, marked as C-10.
[0216] Reaction test: 5g of the above catalyst C-10 was placed in a reactor and reduced with 0.2MPa pure H2 at 320℃ for 5h. After the reduction was completed, the temperature was lowered to 290℃, the H2 pressure was raised to 1.5MPa, the H2 space velocity was adjusted to 36000ml / g-cat / h, the reaction raw material was a 50% maleic anhydride / 50% γ-butyrolactone mixed liquid, and a liquid phase pump was used for feeding. The liquid hourly space velocity of maleic anhydride was 1.0g / g-cat / h, the molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 30, and the H2 circulation ratio was 8. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0217] Embodiment 11
[0218] Weigh 564.8g of copper nitrate trihydrate and 624.7g of zinc nitrate hexahydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZn solution with a metal molar concentration of 2.0M, and heat it to 70°C; precipitate the heated CuZn solution with a 2M NaHCO3 solution in parallel, and adjust the pH value to 7; the precipitation time is 1.5h. After the precipitation is completed, add 47.6g of pseudo-boehmite (containing 75wt% of dry Al2O3) to the precipitation reactor and maintain 70°C for stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. The filtered precipitate is dried at 120°C, and calcined to 450°C in a muffle furnace at a heating rate of 2°C / min and maintained for 6 hours to obtain a CuZnAl precursor. Weigh 10.8 g of ferric nitrate nonahydrate and dissolve it in 231 mL of deionized water. Impregnate an equal volume of the prepared CuZnAl precursor sample of 300 g, dry it again at 120°C, and calcine it to 450°C in a muffle furnace at a heating rate of 2°C / min and keep it for 6 hours to obtain a FeCuZnAl precursor. Place FeCuZnAl in an atmosphere furnace, pass a 20% CO-80% N2 mixed gas, heat it to 550°C at a rate of 10°C / min and keep it for 6 hours, extrude it into strips, and obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Fe / C=44.4 / 42.1 / 9.2 / 0.5 / 3.8, marked as C-11.
[0219] Reaction test: 5g of the above catalyst C-11 was placed in a reactor and directly reacted under the reaction conditions of 260°C, 1MPa pressure and H2 space velocity of 41000ml / g-cat / h. The reaction raw material was a 60% maleic anhydride / 40% γ-butyrolactone mixed liquid, and a liquid phase pump was used for feeding. The liquid hourly space velocity of maleic anhydride was 1.5g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 50, and the H2 circulation ratio was 8. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0220] Example 12
[0221] Weigh 564.8g of copper nitrate trihydrate and 624.7g of zinc nitrate hexahydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZn solution with a metal molar concentration of 2.0M, and heat it to 70°C; precipitate the heated CuZn solution with a 2M NaHCO3 solution in parallel, and adjust the pH value to 7; the precipitation time is 1.5h. After the precipitation is completed, add 47.6g of pseudo-boehmite (containing 75wt% of dry Al2O3) to the precipitation reactor and maintain 70°C for stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. The filtered precipitate is dried at 120°C, and calcined to 450°C in a muffle furnace at a heating rate of 2°C / min and maintained for 6 hours to obtain a CuZnAl precursor. Weigh 2.5 g of cobalt nitrate hexahydrate and dissolve it in 238 mL of deionized water, then soak it in a 300 g sample of CuZnAl precursor, dry it again at 120 ° C for 12 h, and calcine it at 450 ° C for 3 h to obtain a CoCuZnAl precursor. Place CoCuZnAl in an atmosphere furnace, introduce a 2% ethylene-98% N2 mixed gas, heat it to 600 ° C at a rate of 8 ° C / min and maintain it for 10 hours, extrude it into strips, and obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Co / C=45.1 / 42.8 / 9.3 / 0.2 / 2.6, marked as C-12.
[0222] Reaction test: 5g of the above catalyst C-12 was placed in a reactor at 270°C, 2MPa pressure and H2 space velocity of 40000ml / g-cat / h. The raw material was a 40% maleic anhydride / 60% γ-butyrolactone mixed liquid, and a liquid phase pump was used for feeding. The liquid hourly space velocity of maleic anhydride was 2.0g / g-cat / h. The molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 40, and the H2 circulation ratio was 10. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured to calculate the conversion rate of maleic anhydride and the product selectivity of the reaction. The reaction results are listed in Table 1.
[0223] Embodiment 13
[0224] Weigh 564.8g of copper nitrate trihydrate and 624.7g of zinc nitrate hexahydrate and dissolve them in an appropriate amount of deionized water to prepare a CuZn solution with a metal molar concentration of 2.0M, and heat it to 70°C; precipitate the heated CuZn solution with a 2M NaHCO3 solution in parallel, and adjust the pH value to 7; the precipitation time is 1.5h. After the precipitation is completed, add 47.6g of pseudo-boehmite (containing 75wt% of dry Al2O3) to the precipitation reactor and maintain 70°C for stirring and aging for 12h; then filter and wash the precipitate until the conductivity of the washing filtrate is 8μs / cm. The filtered precipitate is dried at 120°C, and calcined to 450°C in a muffle furnace at a heating rate of 2°C / min and maintained for 6 hours to obtain a CuZnAl precursor. Weigh 74.3 g of nickel nitrate hexahydrate and dissolve it in 166 mL of deionized water, soak it on a 300 g sample of CuZnAl precursor, dry it again at 120 ° C for 12 h, and calcine it at 550 ° C for 5 h to obtain a NiCuZnAl precursor. Place NiCuZnAl in an atmosphere furnace, introduce a 15% methane-85% N2 mixed gas, heat it to 650 ° C at a rate of 6 ° C / min and maintain it for 0.5 hours, extrude it into strips, and obtain a Φ5×5 mm cylindrical catalyst with an elemental mass composition of CuO / ZnO / Al2O3 / Ni / C=35.4 / 33.6 / 7.4 / 3.8 / 19.8, marked as catalyst C-13.
[0225] Reaction test: 5g of the above catalyst Cat-10 was placed in a reactor, and directly reacted under the reaction conditions of 250°C, 0.5MPa pressure and H2 space velocity of 35000ml / g-cat / h. The reaction raw material was a 65% maleic anhydride / 35% γ-butyrolactone mixed liquid, and a liquid phase pump was used for feeding. The liquid hourly space velocity of maleic anhydride was 1.0g / g-cat / h, and the molar ratio of H2 in the maleic anhydride hydrogenation reaction to the raw material maleic anhydride was 60, and the H2 circulation ratio was 10. During the reaction, the composition of the reaction tail gas and the liquid phase product was analyzed by gas chromatography every 12h, and the acidity of the liquid phase product was measured, which was used to calculate the conversion rate and product selectivity of the maleic anhydride in the reaction. The reaction results are listed in Table 1.
[0226]
[0227] As shown in Table 1, the transition metal-modified CuZnAl catalyst of the present invention has good anti-wear performance, and shows very high maleic anhydride conversion rate and excellent γ-butyrolactone selectivity in maleic anhydride hydrogenation process, wherein the selectivity of γ-butyrolactone can achieve more than 82%, preferably more than 90%, more preferably more than 95%, and even up to 98.5%. Compared with the unmodified catalyst (C-4), the space-time yield of the modified catalyst is higher, the by-products are lower, and the catalyst is more stable in long-term operation. The life of the C-7 catalyst is up to 3100h, and the γ-butyrolactone production capacity of the catalyst is greater than 3500g / g-cat. Compared with the same type of maleic anhydride hydrogenation catalyst, the production capacity of the catalyst is greatly improved, the production cost of γ-butyrolactone can be greatly reduced, and it has broad application prospects.
Claims
1. A CuZnAl catalyst modified by nano-carbon material and transition metal, the catalyst comprising CuO, ZnO, Al2O3, transition metal and nano-carbon material, wherein: The transition metal is at least one of Fe, Co and Ni; the nano-carbon material is at least one of fullerene, carbon nanocage, single-walled nanotube and multi-walled carbon nanotube; the transition metal is coated in the nano-carbon material structure.
2. The catalyst according to claim 1, wherein Relative to the total mass of the catalyst, the mass content of CuO is 15-70wt%; the mass content of ZnO is 5-60wt%; the mass content of Al2O3 is 2-30wt%; the mass content of transition metal is 0.001-5wt%; and the mass content of nano-carbon material is 0.5-20wt%.
3. The catalyst according to claim 1 or 2, wherein The transition metal is coated in the nanocarbon material structure to form one or more structures selected from the following: Fe@fullerene, Co@fullerene, Ni@fullerene, Fe@carbon nanocage, Co@carbon nanocage, Ni@carbon nanocage, Fe@single-walled carbon nanotube, Co@single-walled carbon nanotube, Ni@single-walled carbon nanotube, Fe@multi-walled carbon nanotube, Co@multi-walled carbon nanotube, Ni@multi-walled carbon nanotube.
4. A method for preparing a catalyst according to any one of claims 1 to 3, the method comprising the following steps: (1) using a carbon-containing gas to carbonize a transition metal raw material by chemical vapor deposition to prepare a nano-carbon-coated transition metal composite material; (2) co-precipitating a solution containing three elements of Cu, Zn and Al to prepare an unmodified CuZnAl precipitation precursor; Alternatively, a solution containing the two elements of Cu and Zn is subjected to a coprecipitation treatment, and pseudo-boehmite is added before or after the coprecipitation treatment to prepare an unmodified CuZnAl precipitation precursor; Alternatively, a solution containing three elements of Cu, Zn and Al is co-precipitated with the nano-carbon-coated transition metal composite material obtained in step (1) to prepare a nano-carbon-coated transition metal-modified CuZnAl precipitation precursor; (3) drying, calcining and shaping the unmodified CuZnAl precipitate precursor obtained in step (2) to obtain an unmodified CuZnAl catalyst; Alternatively, the nanocarbon-coated transition metal composite material obtained in step (1) is added to the unmodified CuZnAl precipitate precursor obtained in step (2), followed by drying, calcining, and molding to obtain the CuZnAl catalyst modified with the nanocarbon material and the transition metal; Alternatively, the nano-carbon-coated transition metal-modified CuZnAl precipitate precursor obtained in step (2) is dried, calcined, and formed to obtain the CuZnAl catalyst modified by the nano-carbon material and the transition metal; (4) if no nano-carbon-coated transition metal composite material is added in steps (2) and (3), the unmodified CuZnAl catalyst obtained in step (3) is mixed evenly with the nano-carbon-coated transition metal composite material obtained in step (1), and the mixture is molded to obtain the CuZnAl catalyst modified with the nano-carbon material and the transition metal; Alternatively, a soluble salt solution of transition metals Fe, Co, and Ni is added to the unmodified CuZnAl catalyst obtained in step (3), dried and calcined, carbonized in a carbon-containing atmosphere, and finally molded to obtain the CuZnAl catalyst modified with nano-carbon material and transition metal.
5. The method according to claim 4, wherein in step (1), the temperature of the carbonization treatment is 400-1100°C, the heating rate of the carbonization treatment is 1-30°C / min, and the time of the carbonization treatment is 0.1-10h.
6. The method according to claim 4 or 5, wherein in step (2), the pH value of the coprecipitation treatment is 3-11; the temperature of the coprecipitation treatment is 20-200°C; and the precipitation time of the precipitation treatment is 0.1-100h.
7. The method according to any one of claims 4 to 6, wherein in step (3), the calcination atmosphere is air, nitrogen, argon or a mixture thereof; the calcination temperature is 300-700°C; the calcination heating rate is 0.5-15°C / min; and the calcination time is 2-12h.
8. The method according to any one of claims 5 to 7, wherein in step (4), the temperature of the carbonization treatment is 400-700°C, the heating rate of the carbonization treatment is 5-30°C / min, and the time of the carbonization treatment is 0.05-10h.
9. Use of the CuZnAl catalyst modified with nano-carbon material and transition metal according to any one of claims 1 to 3 or the CuZnAl catalyst modified with nano-carbon material and transition metal prepared by the method according to any one of claims 4 to 8 for preparing γ-butyrolactone by catalyzing maleic anhydride hydrogenation reaction.
10. A method for preparing γ-butyrolactone by hydrogenation reaction of maleic anhydride, the method comprising placing a CuZnAl catalyst modified with a nano-carbon material and a transition metal according to any one of claims 1 to 3 or a CuZnAl catalyst modified with a nano-carbon material and a transition metal prepared by the method according to any one of claims 4 to 8 in a reactor, passing a maleic anhydride raw material and hydrogen into the reactor to contact the catalyst, and directly hydrogenating maleic anhydride into γ-butyrolactone by the catalyst.
Citation Information
Cited By
Method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst
CN119707889A